Sociabilidades no assentamento Santa Eliza-CE: formas de (re)sistência que constroem o viver - Chaves, Renata Paz Cândido (2012)
This paper presents a reflection about the sociability carried out by peasant families as a form of resistance to the socio-economic model of rationality imposed by capital in the field and forms of family organization and collective present in various aspects of life of these subjects for the construction and affirmation of its territory For this, bring to the debate social settings and productive built by families, looking looking to give visibility to the social relations of association between the subjects in the field through the enhancement subjectivities solidarity culture working with the land relative to the nature and actions of living in rural settlement In this perspective work has dialectical and is a case study conducted with the families of Santa Eliza peasant settlement which is located between the towns of Magdalena and Quixeramobim in the Ceará backwood Central The study aimed to analyze the diversity of social relations built by the families of the Settlement Santa Eliza as a form of resistance and build another model of development that prioritizes their knowledge practices and collective actions and as specific identifying the diversity of social and productive activities carried out within the family and community in the Settlement investigate the participation of the community in the different forms of social interaction made in settlement See and understand how they structure social practices in the construction of the territory Accordingly I sought to show how sociability built by peasant families underpinning another paradigm of welfare and development considering their ways of being and living places in a dynamic subjective relationships of kinship neighborhood friendship respect and reciprocity embodied in its concrete reality of production and social organization